Aspect - samoučeči regulacijski sistem za zahtevne procese - Dolanc, Gregor (Ventil (Ljubljana), 2007)
An aspect system is an advanced control system used to control demanding processes, which can be either non-linear or time-variant and may possess some dead time. To ensure its simple configuration and usage, the control system has self-learning abilities, used to automatically tune and optimise the control parameters. The tuning and optimisation is performed using a model of the controlled process, which is built automatically on the basis of the information retrieved from the process during operation. The aspect control system is implemented in terms of a software product that can run on powerful programmable logic controllers.
Keywords: industrijski procesi; krmilniki; regulacija; regulacijski sistemi; samoučeči sistemi